Jean Renart and the art of romance : essays on Guillaume de Dole - Durling, Nancy Vine, 1953- (University Press of Florida, 1997)
In this first volume of critical essays ever devoted to Jean Renart's work, contributors draw on political and social history, women's studies, translation theory, musicology, and literary theory to illuminate Jean's remarkable contribution to the highly complex genre of courtly romance. An extraordinary blend of realism and high artifice, unique in its combined use of songs and narrative, Jean Renart and the Art of Romance offers zestful dalliances in high places, handsome but self-serving knights, and a beautiful woman whose decisive intelligence allows her to triumph over daunting odds. An important contribution to our understanding of thirteenth-century romance, this volume of essays will prove of interest to scholars of medieval French literature, history, musicology, and codicology.